Vitamin E biofortification: enhancement of seed tocopherol concentrations by altered chlorophyll metabolism - Qin, Ping; Chen, Peng; Zhou, Yuanwei; Zhang, Wei; Zhang, Yunyun; Xu, Jingjing; Gan, Lu; Liu, Yingnan; Romer, Jill; Dörmann, Peter; Cahoon, Edgar B.; Zhang, Chunyu (Frontiers in Plant Science, 2024)
Homogentisate Phytyltransferase (HPT) catalyzes condensation of homogentisate (HGA) and phytyl diphosphate (PDP) to produce tocopherols, but can also synthesize tocotrienols using geranylgeranyl diphosphate (GGDP) in plants engineered for deregulated HGA synthesis. In contrast to prior tocotrienol biofortification efforts, engineering enhanced tocopherol concentrations in green oilseeds has proven more challenging due to the integral role of chlorophyll metabolism in supplying the PDP substrate. This study show that RNAi suppression of CHLSYN coupled with HPT overexpression increases tocopherol concentrations by >two-fold in Arabidopsis seeds. We obtained additional increases in seed tocopherol concentrations by engineering increased HGA production via overexpression of bacterial TyrA that encodes chorismate mutase/prephenate dehydrogenase activities. In overexpression lines, seed tocopherol concentrations increased nearly three-fold, and resulted in modest tocotrienol accumulation. We further increased total tocochromanol concentrations by enhancing production of HGA and GGDP by overexpression of the gene for hydroxyphenylpyruvate dioxygenase (HPPD). This shifted metabolism towards increased amounts of tocotrienols relative to tocopherols, which was reflected in corresponding increases in ratios of GGDP/PDP in these seeds. Overall, our results provide a theoretical basis for genetic improvement of total tocopherol concentrations in green oilseeds (e.g., rapeseed, soybean) through strategies that include seed-suppression of CHLSYN coupled with increased HGA production.